Hotel and motel management and operations - Gray, William S.; Liguori, Salvatore C. (Mandaluyong City, Philippines : National Book Store, 1982)
The hotel industry should not be regarded as standing separate and unrelated to other industries, but rather as forming a part of the much larger hospitality industry. It is within this framework that the history of hotel development should be examined.
Preface -- Section one : Hotel and motel development -- Section two : Hotel management -- Section three : Hotel Operations -- Section four : Hotel accounting and controls -- Section five : The Future of the industry
Keywords: HOTEL MANAGEMENT